The Effect of the Guided Inquiry Learning Model on Spatial Thinking Skills and Problem Solving Abilities of Geography Education Students at Tadulako University - Zaenudin Ali; Syamsul Bachri; Didik Taryana (Universitas Sebelas Maret, 2026)
The Guided Inquiry Learning Model emphasizes students’ active engagement in constructing knowledge through a systematic investigation process with instructor support. This study aimed to examine the effect of the Guided Inquiry learning model on the spatial thinking skills and problem solving abilities of Geography Education students in the Geographic Information Systems (GIS) course at the Geography Education Study Program, Tadulako University. The study employed a quasi-experimental design with a pretest posttest control group. Two groups were involved: an experimental group taught using the Guided Inquiry model and a control group taught using conventional instruction. Spatial thinking skills and problem-solving abilities were measured using essay tests that had been validated for reliability and validity. Data were analyzed through normality and homogeneity tests, followed by an Independent Samples t-test using SPSS 25. The results indicated that the experimental group achieved higher posttest mean scores in both spatial thinking skills and problem solving abilities compared to the control group. Statistical analysis showed a significant difference in posttest spatial thinking scores between the experimental and control groups (p < 0.05), as well as a significant difference in problem-solving ability scores (p < 0.05). Furthermore, normalized gain analysis indicated that the experimental group achieved moderate to high gains in both variables, while the control group demonstrated low to moderate gains. These results suggest that the Guided Inquiry learning model is more effective than conventional instruction in improving spatial thinking skills and problem-solving abilities in the Geographic Information Systems course.